Analisis Strategi Peningkatan Produksi Mebel di Sentra Industri Kayu - Sofiana, Yunida (Humaniora, 2011)
In the latest couple years, both public and private sectors are doing some efforts and innovations to promote several arts and furniture in Indonesia; through media, cooperation program and exhibitions all over the world. However, this is not effective enough to increase furniture production to better level, especially regarding micro central industry. The micro central industry, especially wood central industry in several areas in Java, mostly has stagnant condition in both local and international. Based on the research in wood central industry in Java, there are factors as the effects: the scarcity and quality of wood material, technology dominance of limited woods, less innovation in designing, unintegrated promotion and marketing and also less strategic planning from the government to develop minor industry. This needs to be analysed according to the condition and need of minor central industry.